Silicon valley's innovative milieu: a cultural mix of entrepreneurs/ an entrepreneurial mix of cultures? Experiences of European firms - Pohl, Nicole; Heiduk, Günter (ERDKUNDE, 2002)
Silicon Valley is one of the leading high-tech regions in the world. Its companies and workforce are characterized by a high cultural diversity and include many immigrant entrepreneurs and multinationals, among them Europeans. European companies have chosen the region as a location for sales, research and development as well as to establish listening posts. Silicon Valley's success can certainly be traced to the breakthroughs achieved by a group of innovators and entrepreneurs like Hewlett, Packard, Shockley (Shockley Transistor, Fairfield Semiconductor), Jobs/Wozniak (APPLE) or YAHOO founder Jerry Yang. Besides these individual successes, its unique regional culture and its special ecosystem have been stressed as prerequisites for its success. While countries have mostly been taken as the units to analyse the effects of culture on economic behaviour, Silicon Valley's example helps us point out the importance of a set of rules and behaviours that provide a framework for the interactions among individuals with diverse country cultural backgrounds. It is the aim of the study to analyse how European firms integrate into Silicon Valley's innovative milieu and which tensions result for local managers, who are supposed to operate in a two-tier system of business culture: Silicon Valley's network culture and the business norms and behaviours that are valid in their parent company. The results of the study show that - the significance of differences in business culture and the need for local integration is often underestimated by foreign companies, - integration into local networks depends crucially on the socio-cultural competence of individuals in the local management, - successful local integration can lead to increasing socio-cultural distance to the parent company. The study confirms the understanding that global technological leadership is crucially related to collective dynamics and interaction patterns of the local innovation community, which might be described as regional culture. It is also in line with findings in the business literature about the challenges faced by multinational companies operating in diverse cultural environments.